The meaning of the diagnosis in the illness trajectory of a person with rheumatic disease: From the uncertainty to biographical disruption - Rosa María Osorio Carranza (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2017)
This article seeks to analyze the meaning of the medical diagnosis in the biographies of people who suffer from a rheumatic disease. Based in the ethnographic method, in-depth interviews were carried out among fifteen informants affected by different rheumatic conditions from the City of Barcelona. These interviews make it possible to see how the symptoms, dysfunctions or limitations experienced up until the definitive diagnosis can be reinterpreted in the presence of a model that explains the condition and gives it a name, attributing new meaning to the symptoms and establishing certain care and coping strategies. After a period of uncertainty, this definitive medical diagnosis allows for an enigmatic chronic condition from which the person is suffering to be deciphered, representing a turning point in the care trajectory that is understood as a biographical disruption redefining the past and future of the subject. However, it is often necessary for those affected to undergo a complex, erratic and uncertain itinerary to reach the final diagnosis, which is then identified retrospectively as a milestone in the illness experience.